Heparin prevents in vitro glycocalyx shedding induced by plasma from COVID-19 patients - Potje, Simone R.; Costa, Tiago J.; Fraga-Silva, Thais F.C.; Martins, Ronaldo B.; Benatti, Maira N.; Almado, Carlos E.L.; de Sá, Keyla S.G.; Bonato, Vânia L.D.; Arruda, Eurico; Louzada-Junior, Paulo; Oliveira, Rene D.R.; Zamboni, Dario S.; et al. (Life sciences (1973), 2021)
The severe forms and worsened outcomes of COVID-19 (coronavirus disease 19) are closely associated with hypertension and cardiovascular disease. Endothelial cells express Angiotensin-Converting Enzyme 2 (ACE2), which is the entrance door for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The hallmarks of severe illness caused by SARS-CoV-2 infection are increased levels of IL-6, C-reactive protein, D-dimer, ferritin, neutrophilia and lymphopenia, pulmonary intravascular coagulopathy and microthrombi of alveolar capillaries. The endothelial glycocalyx, a proteoglycan- and glycoprotein-rich layer covering the luminal side of endothelial cells, contributes to vascular homeostasis. It regulates vascular tonus and permeability, prevents thrombosis, and modulates leukocyte adhesion and inflammatory response. We hypothesized that cytokine production and reactive oxygen species (ROS) generation associated with COVID-19 leads to glycocalyx degradation. A cohort of 20 hospitalized patients with a confirmed COVID-19 diagnosis and healthy subjects were enrolled in this study. Mechanisms associated with glycocalyx degradation in COVID-19 were investigated. Increased plasma concentrations of IL-6 and IL1-β, as well as increased lipid peroxidation and glycocalyx components were detected in plasma from COVID-19 patients compared to plasma from healthy subjects. Plasma from COVID-19 patients induced glycocalyx shedding in cultured human umbilical vein endothelial cells (HUVECs) and disrupted redox balance. Treatment of HUVECs with low molecular weight heparin inhibited the glycocalyx perturbation. In conclusion, plasma from COVID-19 patients promotes glycocalyx shedding and redox imbalance in endothelial cells, and heparin treatment potentially inhibits glycocalyx disruption. [Display omitted] •Endothelial cells are a crucial interface between blood and tissues, maintaining vascular homeostasis•SARS-CoV-2 infection threatens endothelial function by increasing cytokines and ROS, thus shedding the endothelial glycocalyx•Plasma from COVID-19 patients disrupts the glycocalyx, which is prevented by heparin/LMWH